2011
DOI: 10.1080/17512786.2011.601938
|View full text |Cite
|
Sign up to set email alerts
|

Community Service

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link ABSTRACT:Armed with readily accessible online traffic logs that provide detailed information about the items users are selecting to view, editors are voicing concern about the potential effect on their own content decisions. Through a survey of local British newspaper editors, this article examines the overlap between user preferences, as suggested by assessments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…However, journalists still tend to reject audience feedback even in the era of web analytics (MacGregor, 2007;Singer, 2011;Usher, 2013). This is a continuation of the pattern observed in newsrooms long before the onset of online news: journalists had ignored, if not rejected, audience feedback (Gans, 1979;Schlesinger, 1978).…”
Section: Web Analyticsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, journalists still tend to reject audience feedback even in the era of web analytics (MacGregor, 2007;Singer, 2011;Usher, 2013). This is a continuation of the pattern observed in newsrooms long before the onset of online news: journalists had ignored, if not rejected, audience feedback (Gans, 1979;Schlesinger, 1978).…”
Section: Web Analyticsmentioning
confidence: 88%
“…This pattern of divergence in audience and journalistic preferences persists even with the onset of online news which allows a more accurate monitoring of audience metrics. In general, while journalists usually put more importance on public affairs stories, online audiences are usually more interested in soft news, such as entertainment and sports (Boczkowski, 2010;Boczkowski et al, 2011;Singer, 2011;Thorson, 2008). This divergence also manifests itself in how audiences regard lists of most viewed stories.…”
Section: Divergent Preferencesmentioning
confidence: 99%
“…At a local/community level, particularly, in rural areas, where traditional journalism's domination of public discourse is perhaps most noticeable, citizen journalism has been discussed as a much needed complement, although not always embraced wholeheartedly by professional journalists or editors (Lewis, Kaufhold, and Lasorsa 2009). Naturally, one of the big questions in this context is connected to the possibility of bypassing traditional media's gatekeeping privilege (Bruns 2008;Gillmor 2004;Goode 2009;Singer 2011). Furthermore, citizen journalists also have democratic potential as watchdogs of the watchdogs, by providing independent media-criticism that can expose unethical or untruthful reporting in traditional media and perhaps increase traditional media's accountability to its audience and to society (Holt and von Krogh 2010).…”
Section: Community Journalism and The Promise Of Citizen Journalismmentioning
confidence: 96%
“…Several studies have observed a divide between audiences' and journalists' news values (Boczkowski, Mitchelstein & Walter 2011;Boczkowski & Peer 2011;Lee, Lewis & Powers 2012), while Singer (2011) observed both commonalities and differences. A study by Boczkowski and Mitchelstein (2013) found that journalists' and audience's interests are divergent by default, although this "news gap" closes during certain attention-grabbing news events, like elections.…”
Section: Is There a Chasm Between Journalists And Their Audiences?mentioning
confidence: 99%